Ergonomics Evaluation for Turning Machinists in Oil and Gas Industry - Hj Abu Kasim, Mohd Zul Helmie; Mohd-Taib, Mohd Firdaus (International Journal of Integrated Engineering, 2022)
Initial ergonomics risk assessment conducted on the CNC turning machine shop in oil and gas manufacturing company found the existence of ergonomics risk factors towards machinists during manual handling of the large work piece that may affect the health of the machinists. This study aims to determine and improve the ergonomics risk factor that the machinists may be exposed to. In this study, the data are collected and analysed using Cornell Musculoskeletal Questionnaire, Rapid Entire Body Assessment (REBA) and torque analysis. Analysis result showed that there is one very high risk posture. The root cause was identified using 5 Why methodology where torque wrench design limitation has been identified as the main contributor to the very high REBA score. The improvement action taken was to use the manual torque multiplier equipment to reduce the input torque applied by the machinist and change the location of the tightening torque applied for the clamping and adjusting purposes which have been significantly reduced the REBA score from 11 (very high risk) to 3 (low risk).